2016
DOI: 10.1152/ajpheart.00638.2015
|View full text |Cite
|
Sign up to set email alerts
|

PGE2-EP3 signaling exacerbates intracerebral hemorrhage outcomes in 24-mo-old mice

Abstract: With the population aging at an accelerated rate, the prevalence of stroke and financial burden of stroke-related health care costs are expected to continue to increase. Intracerebral hemorrhage (ICH) is a devastating stroke subtype more commonly affecting the elderly population, who display increased mortality and worse functional outcomes compared with younger patients. This study aimed to investigate the contribution of the prostaglandin E2 (PGE2) E prostanoid (EP) receptor subtype 3 in modulating anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…20,46 Previous studies have confirmed PGE2-EP3 signaling axis in modulating multiple forms of brain disorders, including ischemic and hemorrhagic stroke, and Alzheimer's diseases, using EP3 knockout mice. [47][48][49] In this study, we found that it is the EP3 receptor that dramatically upregulated at both transcription and translation levels after mice received laparotomy, especially in neu- In our study, we also observed that CREB, Arc, and BDNF dramatically decreased after laparotomy in mice. That means the synaptic plasticity mechanism is possibly involved in the development of POCD.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…20,46 Previous studies have confirmed PGE2-EP3 signaling axis in modulating multiple forms of brain disorders, including ischemic and hemorrhagic stroke, and Alzheimer's diseases, using EP3 knockout mice. [47][48][49] In this study, we found that it is the EP3 receptor that dramatically upregulated at both transcription and translation levels after mice received laparotomy, especially in neu- In our study, we also observed that CREB, Arc, and BDNF dramatically decreased after laparotomy in mice. That means the synaptic plasticity mechanism is possibly involved in the development of POCD.…”
Section: Discussionsupporting
confidence: 64%
“…EP3 signaling in response to PGE2 is primarily coupled to Gi protein, which reduces cAMP formation, and therefore termed the “inhibitory” receptor . Previous studies have confirmed PGE2‐EP3 signaling axis in modulating multiple forms of brain disorders, including ischemic and hemorrhagic stroke, and Alzheimer's diseases, using EP3 knockout mice . In this study, we found that it is the EP3 receptor that dramatically upregulated at both transcription and translation levels after mice received laparotomy, especially in neurons, but not other EP receptors (EP1, EP2, and EP4), which may imply the direct influence of EP3 receptors on neuronal function.…”
Section: Discussionmentioning
confidence: 57%
“…EP3 receptor is the most abundant receptor in brain (Leclerc et al, 2016) and appears to play an important role in acute ischemic stroke. A study showed that activation of EP3 receptor with ONO-AE-248 increased infarct size in experimental stroke (Ahmad et al, 2007).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The main models discussed in this section represent major risk factors for ICH in patients: hypertension, cerebral amyloid angiopathy (CAA) and cerebral small vessel disease (CSVD). The HEADS committee also highlighted the need to develop models of modifiable and non-modifiable risk factors, such as alcoholism and ageing to further understand how ICH can be prevented in these populations, as there are relatively few papers which utilise these risk factors [20,[56][57][58][59][60][61][62][63].…”
Section: Spontaneous Haemorrhage Modelsmentioning
confidence: 99%